Activated carbon derived from Japanese distilled liquor waste: Application as the electrode active material of electric double-layer capacitors. (20th June 2020) - Eguchi, Takuya; Tashima, Daisuke; Fukuma, Masumi; Kumagai, Seiji
Abstract: Shochu is a major distilled liquor in Japan, and significant shochu waste (approximately one million metric tons) is discharged every year. Wheat shochu waste was precarbonized at 600 or 700 °C and then processed by KOH chemical activation, producing shochu waste-derived activated carbon (SWAC). The material properties and electrochemical performance of SWAC were investigated to verify its potential use as the electrode active material of electric double-layer capacitors (EDLCs), in comparison with two types of commercially available benchmark activated carbons. The precarbonization temperature had a significant influence on not only the development of pores but also the energy and power densities of the SWACs. Among all the samples, the SWAC precarbonized at 700 °C, with a specific surface area of 2434 m 2 g −1, exhibited the highest gravimetric specific capacitance of 152 F g −1 and the highest gravimetric energy density of 44 Wh kg −1 . The SWAC precarbonized at 600 °C achieved the highest volumetric specific capacitance of 75 F cm −3 and a volumetric energy density of 18 Wh L −1 but displayed low power performance. The performance of EDLC electrodes using this distilled liquor-originated biowaste was highly promising. Graphical abstract: Image 10980 Highlights: Activated carbons from distilled liquor waste was produced using KOH activation. The activated carbon was tested as an electric double-layer capacitor electrode. The precarbonization temperature was important for the electrode's performance. A relation between the textural property and electrode performance was studied. The superior performance was attributed to a well-balanced micropore distribution.